Principles of financial management - Curran, Ward S. (New York : McGraw-Hill Book Company, 1970)
This book is designed for use in a one-quarter or one-semester introductory course in business finance, whether the course is taught in a business school or in an economics curriculum of a liberal arts college. The book of course, make use of numerous ideas of authors who have contributed to the growing body of literature in business finance.
Includes bibliographic references and index.
hza 15/10/2018
Loans
Keywords: Financial management; Corporation - finance